2013
DOI: 10.14453/aabfj.v7i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Compliance and Discretionary Accruals: New Zealand Evidence

Abstract: The purpose of this paper is to investigate the effect of better compliance with corporate governance regulation on managerial accruals (discretionary accruals) in New Zealand listed companies. Unlike previous research of earnings management, Jones model (Jones 1991), Modified Jones model and Performance Matched Accruals Model (Kothari, Leone, & Wasley, 2005) this research focuses on free cash flow as a measure of discretionary accruals instead of cash flow from operating activities. Univariate and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
2
20
0
2
Order By: Relevance
“…In NZ, there is a tendency in favour of a soft regulation strategy of equal opportunities, peer pressure and knowledge-sharing (Casey et al , 2011). Moreover, NZ corporate regulation is comparatively more flexible than USA where management is strictly monitored, controlled and penalised for wrong forecast and earnings engineering (Bhuyian et al , 2013). A study by Bhuyian et al , 2013 found evidence that the “comply or explain” nature of soft regulation is effective in NZ and that it reduces managerial discretionary accruals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In NZ, there is a tendency in favour of a soft regulation strategy of equal opportunities, peer pressure and knowledge-sharing (Casey et al , 2011). Moreover, NZ corporate regulation is comparatively more flexible than USA where management is strictly monitored, controlled and penalised for wrong forecast and earnings engineering (Bhuyian et al , 2013). A study by Bhuyian et al , 2013 found evidence that the “comply or explain” nature of soft regulation is effective in NZ and that it reduces managerial discretionary accruals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that firms with higher corporate governance compliance have reduced opportunistic management attitudes which ensure higher accountability and reporting quality (Aguilera, 2005; Sinha, 2006). A study by Bhuyian et al (2013) found that corporate governance compliance increase management’s accountability and reduce financial discretion in decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this analysis is driven by research that indicates the impact of governance characteristics and institutional settings on earnings management behavior (e.g. Koh, 2003;Reverte, 2008;Epps and Ismail, 2009;Kent et al, 2010;Bhuiyan et al, 2013) as well as recent contributions to the UK literature that document the important effect of some corporate governance mechanisms raised by the Higgs Report (2003) in reducing earnings management activities (Iqbal and Strong, 2010;Habbash et al, 2013a;2013b).The findings of the current study show some evidence of income-increasing pre-merger accrual-based earnings management by stock-financed acquirers in the full sample of years 1990-2009. However, there does not appear to be any changes across periods before and after the enactment of the Higgs recommendations.…”
mentioning
confidence: 99%
“…The impact of certain performance indicators is quantified to this end, using indicators such as earnings per share (EPS), book-to-market ratio (BMR) [8], leverage and company size [9,10]. Complementary to these financial indicators, an analysis is performed on the dependence of financial information quality (magnitude of DAC) on variables such as the quality of corporate governance [11,52], the specifics of accounting standards, or the auditor's reputation [12].…”
Section: The Role Of Financial Information Quality In Substantiating the Investment Decisionmentioning
confidence: 99%